2014
DOI: 10.1038/onc.2014.61
|View full text |Cite
|
Sign up to set email alerts
|

The transcriptional modulator BCL6 as a molecular target for breast cancer therapy

Abstract: Inappropriate expression or activation of transcription factors can drive patterns of gene expression leading to the malignant behavior of breast cancer cells. We have found that the transcriptional repressor BCL6 is highly expressed in breast cancer cell lines, and its locus is amplified in about half of primary breast cancers. To understand how BCL6 regulates gene expression in breast cancer cells, we utilized ChIP-seq to identify the BCL6 binding sites on a genomic scale. This revealed that BCL6 regulates a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
93
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(96 citation statements)
references
References 38 publications
3
93
0
Order By: Relevance
“…16 Moreover, it is also found in many tissues such as skeletal muscle, breast and prostate. 17,18 In support of this observation, recent studies have uncovered that deregulation of BCL6 is involved in breast cancer development by blocking differentiation of breast epithelia cells, [18][19][20] suggesting that BCL6 exerts similar function in non-haematopoietic cells as well.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…16 Moreover, it is also found in many tissues such as skeletal muscle, breast and prostate. 17,18 In support of this observation, recent studies have uncovered that deregulation of BCL6 is involved in breast cancer development by blocking differentiation of breast epithelia cells, [18][19][20] suggesting that BCL6 exerts similar function in non-haematopoietic cells as well.…”
Section: Introductionmentioning
confidence: 67%
“…18,19 A recent study has further revealed that BCL6 expression promotes proliferation and survival of breast cancer cells and inhibiting BCL6 leads to apoptosis of these cells by targeting a cohort of genes. 20 It has been reported that proliferation and apoptosis of trophoblasts are deregulated in preeclamptic placentas. [42][43][44] Interestingly, an increase in the mRNA of BCL6 in preeclamptic placentas has been observed independently by several groups, [21][22][23]26 yet its roles in the development of preeclampsia remain to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not detect any binding of BCL6 to the E-cadherin promoter (data not shown). A number of studies demonstrate that a variety of transcriptional repressors including Snail, Twist, Slug, deltaEF1/ZEB1, SIP1/ZEB2 and CtBP2 can bind to the E-cadherin promoter and inhibit the gene transcription [5][6][7][8][9][10][11][12]. We therefore screened which transcription repressor mediated the BCL6-repressed E-cadherin expression with siRNA assay.…”
Section: Bcl6 Promotes Emt Through Enhancing the Zeb1-mediated Transcmentioning
confidence: 99%
“…By binding to specific DNA sequences, BCL6 controls the transcriptional expression of target genes involved in the pathogenesis of B-cell lymphomas or breast cancers [6,7]. Once it binds to the target DNA sequences, BCL6 recruits corepressor SMRT, NCOR or BCOR through its BTB domain and regulates cellular proliferation and survival [8].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation